Coal and Gas Outburst Affected by Law of Small Fault Instability during Working Face Advance. (28th October 2020) - Lin, Jianyun; Zuo, Yujun; Zhang, Kai; Sun, Wenjibin; Jin, Biao; Li, Taotao; Chen, Qing-gang
Abstract : To analyze the effect of small faults in the working face on coal and gas outbursts, the coal and gas outburst accident in the 21431 working face was studied with the 3DEC numerical simulation method, and the main research contents were the change laws of both stresses at the small fault and the overburden strata movement rate in the small fault zone of which the drop height and the strike were designed into different groups. The results show that the risk of small fault slip increases with the advancing working face. In addition, there is a positive correlation between the risk and the small fault throw. The movement rate of overburden strata in the small fault zone increases along with the rising of the small fault throw, which increases the energy transferred to the coal seam from the surrounding rock under the effect of the small fault. Hence, the effect of small faults on the working face on coal and gas outbursts was positively correlated with the small fault throw. Under the influence of a small fault strike, the closer it is to the small fault along the dip distance at the same working face, the greater the risk will be of a coal and gas outburst. And the bigger the small fault strike is, the greater is the stress concentration degree in front of the working face and the more the elastic energy is stored and the greater is the possibility of an outburst. The paper analyzes the influence of small faults on coal and gas outbursts in the working face, which has reference significance for the prediction and prevention of coal and gas outburst disaster in the working face.